2015
DOI: 10.1007/s10441-015-9249-9
|View full text |Cite
|
Sign up to set email alerts
|

A Conceptual Model of Morphogenesis and Regeneration

Abstract: This paper is devoted to computer modelling of the development and regeneration of multicellular biological structures. Some species (e.g., planaria and salamanders) are able to regenerate parts of their body after amputation damage, but the global rules governing cooperative cell behaviour during morphogenesis are not known. Here, we consider a simplified model organism, which consists of tissues formed around special cells that can be interpreted as stem cells. We assume that stem cells communicate with each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…Moreover, this is one illustration of the fact that the bioelectric pattern is not an epiphenomenon reflecting current tissue state, but an information structure that will determine (drive the outcome of) future regenerative events. We are currently modeling the state space of bioelectric circuits upstream of morphogen gradients in planaria to identify “edge of chaos” effects in which very similar starting conditions can drive fragments to end up in highly distinct regions of the planarian anatomical morphospace …”
Section: Bioelectric Flatworms: Permanent But Stochastic Re‐writing Omentioning
confidence: 99%
“…Moreover, this is one illustration of the fact that the bioelectric pattern is not an epiphenomenon reflecting current tissue state, but an information structure that will determine (drive the outcome of) future regenerative events. We are currently modeling the state space of bioelectric circuits upstream of morphogen gradients in planaria to identify “edge of chaos” effects in which very similar starting conditions can drive fragments to end up in highly distinct regions of the planarian anatomical morphospace …”
Section: Bioelectric Flatworms: Permanent But Stochastic Re‐writing Omentioning
confidence: 99%
“…Analogous cases have been provided by studies stressing the importance of endogenous, weak electro-magnetic fields in regulating morphogenesis, left-right patterning and many other developmental processes (Pai et al 2015;Tosenberger et al 2015). Moreover, a study concluded that depolarization of a glycine receptorexpressing channel in Xenopus Laevis neural crest may induce a full metastatic melanoma without any involvement of a mutation, carcinogen, or DNA damage (Blackiston et al 2011).…”
Section: Toft and Organicismmentioning
confidence: 88%
“…; Tosenberger et al. ) and dynamic systems descriptions of anatomical attractors (Friston et al. ), attempting a multi‐scale understanding of the planarian's remarkable shape homeostasis.…”
Section: Discussionmentioning
confidence: 99%